2020
DOI: 10.1021/acsami.0c14639
|View full text |Cite
|
Sign up to set email alerts
|

MOF Nanosheet-Based Mixed Matrix Membranes with Metal–Organic Coordination Interfacial Interaction for Gas Separation

Abstract: In the mixed matrix membrane (MMM), the interface between the filler and the polymer matrix will directly affect the gas separation performance of the membranes. Reasonable interfacial design in MMMs is thus important and necessary. In this work, metal−organic coordination interaction is used to construct the interface in metal−organic framework (MOF) nanosheetbased polyimide MMMs where ultrathin Co-benzenedicarboxylate MOF nanosheets (CBMNs) with a thickness less than 5 nm and a lateral size more than 5 μm ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(38 citation statements)
references
References 55 publications
0
38
0
Order By: Relevance
“…At the high content of MOF particles (15, 20, and 50 wt%), the aggregation of UiO-66-NH 2 in the polymeric matrix was observed ( Figure 7 E–G and Figure S2 ). It is reported that the MOF aggregation in polymeric matrix could lead to the formation of non-selective defects during the fabrication process [ 36 ]. Similar phenomenon was observed by Sutrisna et al [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…At the high content of MOF particles (15, 20, and 50 wt%), the aggregation of UiO-66-NH 2 in the polymeric matrix was observed ( Figure 7 E–G and Figure S2 ). It is reported that the MOF aggregation in polymeric matrix could lead to the formation of non-selective defects during the fabrication process [ 36 ]. Similar phenomenon was observed by Sutrisna et al [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Despite the high promise of using MOF nanosheets in MMMs for H2 separation, one of the key challenges lies in the production of high-quality MOF nanosheets to support the largescale membrane fabrication [114]. [113], Copyright 2020 American Chemical Society, and (b) a schematic showing the preparation of the oriented and penetrating ZIF-7@PI MMM. Reprinted with permission from ref.…”
Section: Mof-based Membranesmentioning
confidence: 99%
“…MMM with 20% ZIF-L-Co showed the best H 2 permeability at 1986 barrer. Bi et al also incorporated ultrathin Co-benzenedicarboxylate MOF nanosheets (CBMNs) into a 6FDA-Durene-DABA matrix ( Figure 6 a), leading to improved H 2 separation with a H 2 /CH 4 selectivity of up to 42 [ 113 ]. Recently, Ma et al proposed a new concept of fabricating MMMs [ 85 ].…”
Section: Mixed-matrix Membranes For Hydrogen Separationmentioning
confidence: 99%
See 2 more Smart Citations